The metallobiochemistry of ultratrace levels of platinum group elements in the rat. Issue 2 (11th March 2015) - Sabbioni, E.; Fortaner, S.; Manenti, S.; Groppi, F.; Bonardi, M.; Bosisio, S.; Di Gioacchino, M.
<x xml:space="preserve">Abstract</x> The use of platinum, palladium and rhodium (Platinum Group Elements – PGEs) and the possibility of exposure to their ultratrace levels is increasing.